Synthesis of hexahydroxy strontium stannate nanorods for photocatalytic degradation of organic pollutants. Issue 4 (21st April 2021) - Xue, Zeyang; Li, Feiyang; Yu, Chunhu; Huang, Jianfeng; Tao, Feihu; Cai, Zhengyu; Pei, Lizhai
Abstract: Hexahydroxy strontium stannate nanorods were synthesized via a facile hydrothermal route and characterized by X-ray diffraction, electron microscopy, X-ray photoelectron spectroscopy and solid UV-Vis diffuse reflectance spectroscopy. The nanorods with single crystalline hexagonal SrSn(OH)6 phase have lengths of several μm and diameters of 50–150 nm. The formation process was investigated by observing the evolution of the morphology and structure under different conditions. The band gap is 3.76 eV. The photocatalytic performance of the nanorods was evaluated under ultraviolet light irradiation with crystal violet in aqueous solution which can be entirely photo-degraded within 6 hours. Anti-interference experiments showed that hydroxyl radicals, holes, and superoxide radicals are involved in the sdegradation of crystal violet.